2021
DOI: 10.3390/ijms22020843
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoxia on the Expression of CXC Chemokines and CXC Chemokine Receptors—A Review of Literature

Abstract: Hypoxia is an integral component of the tumor microenvironment. Either as chronic or cycling hypoxia, it exerts a similar effect on cancer processes by activating hypoxia-inducible factor-1 (HIF-1) and nuclear factor (NF-κB), with cycling hypoxia showing a stronger proinflammatory influence. One of the systems affected by hypoxia is the CXC chemokine system. This paper reviews all available information on hypoxia-induced changes in the expression of all CXC chemokines (CXCL1, CXCL2, CXCL3, CXCL4, CXCL5, CXCL6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 323 publications
(275 reference statements)
4
94
0
1
Order By: Relevance
“…Studies in humans and mice have shown that during labor, immune cells such as leukocytes and neutrophils flow into the myometrium and the cervix; the increase in pro-inflammatory cytokines, chemokines, and cell adhesion molecules further amplify inflammation in the labor process ( 34 36 ). In our transcriptomic analysis, the neutrophil chemokines CXCL1 and CXCL8 ( 30 ) and the monocyte/macrophage chemokine CCL2 ( 37 ) were notably upregulated in the IL myometrium, signifying that neutrophils and macrophage are more abundant during labor. The augmentation in multiple CC chemokines, CXC chemokines, and interleukin in the IL myometrium indicated the formation of a proinflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies in humans and mice have shown that during labor, immune cells such as leukocytes and neutrophils flow into the myometrium and the cervix; the increase in pro-inflammatory cytokines, chemokines, and cell adhesion molecules further amplify inflammation in the labor process ( 34 36 ). In our transcriptomic analysis, the neutrophil chemokines CXCL1 and CXCL8 ( 30 ) and the monocyte/macrophage chemokine CCL2 ( 37 ) were notably upregulated in the IL myometrium, signifying that neutrophils and macrophage are more abundant during labor. The augmentation in multiple CC chemokines, CXC chemokines, and interleukin in the IL myometrium indicated the formation of a proinflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 81%
“…A large number of chemokines and cytokines were highly expressed in the IL myometrium; the immune cells (macrophage, T cell, and neutrophil) were activated as well. Many studies have established that hypoxia induces inflammation ( 29 , 30 ) and that it regulates transcription factors in immune cells including HIF and NF-κB, both of which contribute to macrophage polarization, neutrophil survival, and interferon synthesis; however, these factors also restrict NK cytotoxicity in innate immunity. Considering the adaptive immune cell activity, hypoxia mainly anti-T cell inflammation and pro-B cell survival, and immune cells releasing cytokines, chemokines, and matrix metalloproteinase can further promote inflammation ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The research group of Dr. Mojgan Karimabad found increased serum levels of CXCL1 and CXCL12, chemokines with pro-angiogenic properties [ 246 , 247 , 248 ], in neonates from GDM mothers, whereas antiangiogenic chemokines CXCL9 and CXCL10 were downregulated, compared to neonates from healthy mothers without GDM [ 249 ]. In addition, upregulated expression and activity of MMP-2 and MMP-9 and downregulated expression of TIMP-2 has been observed in trophoblasts under hyperglycemic treatment (30 mM), favoring endothelial cell migration during angiogenesis [ 240 ].…”
Section: Endovascular Changes In Gdm: Endothelial Dysfunction and Overstimulation Of Placental Angiogenesismentioning
confidence: 99%
“…Carbonic anhydrase IX (CA IX) directed nanoparticles containing apoptosis inducer, revealed remarkable tumor core penetration accompanied with repolarization of TAMs [ 60 ]. Moreover, under ischemia circumstances, the homing of stem cells relies on the chemokine SDF-1α and its receptor CXCR4 [ 61 ]. Jiang et al targeted tumor hypoxia with nanoparticle-engineered CXCR4-overexpressing adipose-derived stem cells [ 62 ].…”
Section: Remodeling Tumor Angiogenesis Induced Hypoxic Microenvironmentmentioning
confidence: 99%